Long-term in vivo resistin overexpression induces myocardial dysfunction and remodeling in rats - Chemaly, Elie R.; Hadri, Lahouaria; Zhang, Shihong; Kim, Maengjo; Kohlbrenner, Erik; Sheng, Jipo; Liang, Lifan; Chen, Jiqiu; K-Raman, Purushothaman; Hajjar, Roger J.; Lebeche, Djamel (Journal of molecular and cellular cardiology, 2011)
We have previously reported that resistin induces hypertrophy and impairs contractility in isolated rat cardiomyocytes. To examine the long-term cardiovascular effects of resistin, we induced in vivo overexpression of resistin using adeno-associated virus serotype 9 injected by tail vein in rats and compared to control animals. Ten weeks after viral injection, overexpression of resistin was associated with increased ratio of left ventricular (LV) weight/body weight, increased end-systolic LV volume and significant decrease in LV contractility, measured by the end-systolic pressure volume relationship slope in LV pressure volume loops, compared to controls. At the molecular level, mRNA expression of ANF and β-MHC, and protein levels of phospholamban were increased in the resistin group without a change in the level of SERCA2a protein expression. Increased fibrosis by histology, associated with increased mRNA levels of collagen, fibronectin and connective tissue growth factor were observed in the resistin-overexpressing hearts. Resistin overexpression was also associated with increased apoptosis in vivo, along with an apoptotic molecular phenotype in vivo and in vitro. Resistin-overexpressing LV tissue had higher levels of TNF-α receptor 1 and iNOS, and reduced levels of eNOS. Cardiomyocytes overexpressing resistin in vitro produced larger amounts of TNFα in the medium, had increased phosphorylation of IκBα and displayed increased intracellular reactive oxygen species (ROS) content with increased expression and activity of ROS-producing NADPH oxidases compared to controls. Long-term resistin overexpression is associated with a complex phenotype of oxidative stress, inflammation, fibrosis, apoptosis and myocardial remodeling and dysfunction in rats. This phenotype recapitulates key features of diabetic cardiomyopathy. This article is part of Special Issue Item Group entitled "Possible Editorial". ► The long-term in vivo cardiovascular effects of resistin are investigated using AAV9. ► Resistin overexpression in the myocardium induced systolic dysfunction. ► Molecular markers of stress and hypertrophy are increased by resistin in vivo. ► Resistin overexpression induced oxidative stress, myocardial fibrosis and apoptosis. ► Resistin-induced oxidative stress may underlie mechanism governing cardiac remodeling.